Exploring the Enablers and Disablers of Effective Knowledge Transfer within a Cross-cultural Context: The Case of a Japanese MNC in West Java, Indonesia - Wakimura, Kiu; Indriati, Fibria (Technium Social Sciences Journal, 2022)
The purpose of this paper is to explore the enablers and disablers of effective knowledge transfer in cross-cultural contexts. In MNCs knowledge is considered to be a primary source of competitive advantage while effective knowledge transfer across the headquarters and its foreign subsidiary entails attention to the divergence of culture, prejudice, and country-specific business practices. Knowledge actors in such settings are required to have the ability to promulgate knowledge known as disseminative capacity along with the ability to understand and apply external knowledge known as absorptive capacity. This research adopted a qualitative approach using an exploratory case study where expatriates from a foreign subsidiary of Japanese manufacturing MNC in West Java, Indonesia were asked to respond to in-depth interview sessions. Interpretive grounded theory framework and procedures were used for data analyses of the results. The findings suggest that MNCs need to promote communication and linguistic skill training to further develop disseminative capacity and absorptive capacity among the members as well as to design a management strategy that stimulates trust, empathy and a shared vision that can overcome cultural differences within the organization.